Rescue of hepatic phospholipid remodeling defect in iPLA2β-null mice attenuates obese but not non-obese fatty liver - Chamulitrat, Walee; Jansakun, Chutima; Li, Huili; Liebisch, Gerhard (Biomolecules, 2020)
Polymorphisms of group VIA calcium-independent phospholipase A2 (iPLA2β or PLA2G6) are positively associated with adiposity, blood lipids, and Type-2 diabetes. The ubiquitously expressed iPLA2β catalyzes the hydrolysis of phospholipids (PLs) to generate a fatty acid and a lysoPL. We studied the role of iPLA2β on PL metabolism in non-alcoholic fatty liver disease (NAFLD). By using global deletion iPLA2β-null mice, we investigated three NAFLD mouse models; genetic Ob/Ob and long-term high-fat-diet (HFD) feeding (representing obese NAFLD) as well as feeding with methionine- and choline-deficient (MCD) diet (representing non-obese NAFLD). A decrease of hepatic PLs containing monounsaturated- and polyunsaturated fatty acids and a decrease of the ratio between PLs and cholesterol esters were observed in all three NAFLD models. iPLA2β deficiency rescued these decreases in obese, but not in non-obese, NAFLD models. iPLA2β deficiency elicited protection against fatty liver and obesity in the order of Ob/Ob › HFD » MCD. Liver inflammation was not protected in HFD NAFLD, and that liver fibrosis was even exaggerated in non-obese MCD model. Thus, the rescue of hepatic PL remodeling defect observed in iPLA2β-null mice was critical for the protection against NAFLD and obesity. However, iPLA2β deletion in specific cell types such as macrophages may render liver inflammation and fibrosis, independent of steatosis protection.